Changes in Chemo-Enzymatic properties of Soil under Different Drip Irrigation and Fertigation Levels with Cow Urine and Biofertilizers in Protected Condition - Kumar, Sunil; Datt, Naveen; Singh, Manpreet; Kurbah, Ibajanai (International Journal of Bio-resource and Stress Management, 2017)
The effect of different levels of fertigation and drip irrigation was studied along with applications of cow urine and biofertilizers on chemo enzymatic and biological properties of soil during summer season in a naturally ventilated poly house. The experiment was laid out in a randomized block design with 11 treatments and 3 replication comprising of two drip irrigation levels viz., I2 (IW/CPE=0.4) and I4 (IW/CPE=0.8), five fertigation levels, one farmers’ practice and applications of cow urine and biofertilizers. The ammonical (NH4) and nitrate (NO3) forms of soil nitrogen content in treatments F2I4 and F2I2 (where F2 is 100% of recommended NPK doses (1/3rd N and full P, K applied as basal and 2/3rdN through fertigation+Azotobacter+PSB) and 5% cow-urine) were significantly superior then farmers’ practice (T11) at both depths (0.0-0.15 m and 0.15-0.30m). Similarly, trends followed by the biomass carbon, urease and phosphatase activity at both depths. The urease activity was higher in treatments with application of cow urine than without cow urine. The overall results indicated that combined application of bio-fertilizers and fertilizers along with cow urine has positive effect on biomass carbon and chemo- enzymatic properties of soil due to enhanced of soil physical and microbiological properties and addition of nutrients in soil with saving of at least 50 % of water and hence can be exploited as a sustainable approach under integrated nutrient management.